2017
DOI: 10.1111/acel.12574
|View full text |Cite
|
Sign up to set email alerts
|

Increased Arf/p53 activity in stem cells, aging and cancer

Abstract: SummaryArf/p53 pathway protects the cells against DNA damage induced by acute stress. This characteristic is the responsible for its tumor suppressor activity. Moreover, it regulates the chronic type of stress associated with aging. This is the basis of its anti‐aging activity. Indeed, increased gene dosage of Arf/p53 displays elongated longevity and delayed aging. At a cellular level, it has been recently shown that increased dosage of Arf/p53 delays age‐associated stem cell exhaustion and the subsequent decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 69 publications
0
39
0
Order By: Relevance
“…5a). Whereas p16Ink4a inhibits cyclin-dependent kinases, p19Arf indirectly stabilizes p53; and both proteins regulate cell-cycle progression and apoptosis 43,44 .
Fig. 5Ezh2 promotes T FH differentiation by epigenetically repressing Cdkn2a .
…”
Section: Resultsmentioning
confidence: 99%
“…5a). Whereas p16Ink4a inhibits cyclin-dependent kinases, p19Arf indirectly stabilizes p53; and both proteins regulate cell-cycle progression and apoptosis 43,44 .
Fig. 5Ezh2 promotes T FH differentiation by epigenetically repressing Cdkn2a .
…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it regulates the chronic type of stress associated with aging. Indeed, decreased gene dosage of p53 displays elongated longevity and delayed aging [ 58 ]. Previous studies indicated that TERT suppression-induced DNA damage and apoptosis was in a p53-dependent way [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems that CYLD, like other well-known tumor suppressor proteins such as Ink4a, Arf and PTEN, acts as a tumor suppressor in a variety of malignancies. It is interesting that these other renowned tumor suppressors develop important additional roles protecting from aging [1416]. However, the possible role of CYLD as an aging guard has not been yet investigated.…”
Section: Introductionmentioning
confidence: 99%